MANAJEMEN PENGELOLAAN KELAS DALAM RANGKA MEMBENTUK AKUNTABILITAS INDIVIDUAL SISWA - Rohmatul Hidayanti, Erielia; Triyanto, Teguh (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2023)
Classroom management is one part of the substance of school management, where in the classroom students will carry out the learning process in it. A teacher in this case must be able to condition the class so that it can run in a conducive and meaningful way for students. This article was compiled with the aim of knowing how the influence given by the class in forming an accountable attitude to students. The method used in this case is descriptive qualitative method. The results showed that in forming an accountable attitude to students, a teacher must pay attention to the learning methods carried out, the learning environment, climate, class and class discipline.